Overcoming secondary stress in medical and nursing practice : a guide to professional resilience and personal well-being - Wicks, Robert J. (Oxford University Press, 2006)
Suitable for physicians, nurses, and allied health professionals, this book helps them understand acute and chronic secondary stress, develop a personally designed self-care protocol, and strengthen one's inner life. It also features a "Medical-Nursing Professional Secondary Stress Self-Awareness Questionnaire" that can be self-administered